Effects of formaldehyde exposure on granule cell number and volume of dentate gyrus: A histopathological and stereological study - Aslan, Huseyin; Songur, Ahmet; Tunc, Ayten Turkkani; Ozen, Oguz Asian; Bas, Orhan; Yagmurca, Murat; Kaplan, Suleyman (Elsevier, 2006)
The hippocampal formation is a complex region of the brain related to memory and learning. The purpose of the present study was to determine whether exposure of neonatal rats to formaldehyde (FA) had either early or delayed effects on the numbers of granule cells in the dentate gyrus (DG). After birth, the neonatal male Wistar rats were exposed throughout a 30-day period to various concentrations of FA: 0 (control group), 6 ppm (low concentration group) and 12 ppm (high concentration group). This was done by placing them for 6 h/day and 5 days per week in a glass chamber containing FA vapor. Then, five animals from each group were anesthetized and decapitated on postnatal day (PND) 30, and the remaining five animals were sacrificed on PND 90 by intracardiac perfusion using 10% neutral buffered FA solution. The Cavalieri principle of stereological approaches was used to determine the volume of the DG in these sections. The optical fractionator counting method was used to estimate the total number of granule cells in the DG. The appearance of granule cells was normal under light microscopy in all PND 30 and PND 90 groups. There were significant age-related reductions in the volume of the DG at PND 90 irrespective of which group was examined. Significant age-related neuron loss was also determined at PND 90 compared to that at PND 30. Rats treated with a high concentration FA were found to have fewer granule cells than either the animals treated with a low concentration FA or the control group (p < 0.01 and p < 0.01, respectively) at PND 90 but not at PND 30. These findings clearly indicate that granule cells in the DG may be vulnerable to stress and the concentration of FA to which they are exposed during early postnatal life, and also that a neurotoxic effect of high dose FA on cell number is only seen after a long time period. These results may explain why some disorders do not appear until later life. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: formaldehyde; dentate gyrus; neuron; stereology; development; rat